2021
DOI: 10.30560/ier.v4n1p18
|View full text |Cite
|
Sign up to set email alerts
|

Designing Online Learning Evaluation in Times of Covid-19 Pandemic

Abstract: The research objective is to design of learning evaluation that becomes strategy in the Covid Pandemic 19. The study used qualitative research methods with case studies that construct unique and important special realities through data collection interviews and discussions by using case study analysis. The data was collected through online media such as google meetings as well as direct observation from informants, who were determined by purposive sampling, namely the management and student representatives of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…It is in line with a previous study that shows Moodle use could improve students' physics conceptual understanding . Besides, several types of research have also shown that the use of innovative and various media increases students' enthusiasm in the learning activity (Bestari et al 2020;Huwaidi et al 2021;Suswanto et al 2021). It is expected to lessen the impact of online learning experienced by the students including the change of sudden learning style caused by the COVID-19 pandemic (Ratu et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…It is in line with a previous study that shows Moodle use could improve students' physics conceptual understanding . Besides, several types of research have also shown that the use of innovative and various media increases students' enthusiasm in the learning activity (Bestari et al 2020;Huwaidi et al 2021;Suswanto et al 2021). It is expected to lessen the impact of online learning experienced by the students including the change of sudden learning style caused by the COVID-19 pandemic (Ratu et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…(2) Evaluation of program implementation is focused on the quality of the tutorial process. (3) Evaluation of program results is focused on satisfaction with the learning outcomes (Farmer & Koehler, 2022;Ferdianto & Rusman, 2018;Hardman, 2005;Jones, 2012;Schröter & Alyami, 2012;Sabiq et al, 2021).…”
Section: The Standardization Of Innovative Education In the Covid-19 Eramentioning
confidence: 99%
“…The development of online digital media for learning must be increased not only during a pandemic, but it has to become a necessity and a challenge in the digital era as a form of E-Learning (Electronic Learning) process. An electronic learning system with computer and internet technology can support a learning process remotely without having to meet face-to-face between teachers and students (Amichai, 2009;Aviram & Dotan, 2009;Babbar & Gupta, 2022;Clark & Gibb, 2006;Greitzer, 2002;Michael, 2003;Schweizer, 2004;Suswanto et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Nature-Based Learning model provides facilities for all the development of children's abilities such as moral and religious values, cognitive abilities, language skills, physical motor skills, and social-emotional abilities, artistic abilities. An environmental-based education model that involves moral values and local wisdom in their environment as topics in learning activities with topics that are familiar with everyday life [9][10] [11][12][13] [14].…”
Section: Introductionmentioning
confidence: 99%